Bicameral riksdag: Register - Språkbanken Text (University of Gothenburg, 2024)
Part of the data set "Bicameral Riksdag"

Del av Tvåkammarriksdagen
Tvåkammarriksdagen: Register
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik